Potential of Novel Methyl Jasmonate Analogs as Anticancer Agents to Metabolically Target HK-2 Activity in Glioblastoma Cells - Uludağ, Damla; Bay, Sadık; Sucu, Bilgesu Onur; Şavluğ İpek, Özgecan; Mohr, Thomas; Güzel, Mustafa; Karakaş, Nihal (Frontiers in Pharmacology, 2022)
Changes in energy metabolism of cancer cells, which display significant differences compared to normal cells is a rising phenomenon in developing new therapeutic approaches against cancers. One of the metabolic enzymes, Hexokinase-II (HK-II) is involved in glycolysis and inhibiting the HK-II activity may be a potential metabolic target for cancer therapy as most of the drugs in clinical use act on DNA damage. Methyl Jasmonate (MJ) is one of the compounds blocking HK-II activity in cancer cells. In a previous study, we showed that the novel MJ analogues inhibit HK-II activity through VDAC detachment from mitochondria. In this study, to evaluate the potential of targeting HK-2 activity, through patient cohort analysis, we firstly determined HK-2 expression levels and prognostic sigbnificance in highly lethal glioblastoma (GBM) brain tumor. We then examined the in vitro therapeutic effects of the novel analogues in the GBM cells. Here we report that among all, Compound-10 (C-10) showed significant in vitro therapeutic efficacy as compared to MJ which is in use for pre-clinical and clinical studies. Afterwards, we analyzed cell death triggered by C-10 in two different GBM cell lines. We found that C-10 treatment increased the apoptotic/necrotic cells and autophagy in GBM cells. The newly developed analogue, C-10, was found to lethal against GBM by activation of cell death authorities, mostly in a necrotic and autophagic fashion at early stages of the treatment. Considering, possibly decreased intracellular ATP levels by C-10 mediated inhibition of HK-2 activity, and disabled VDAC interaction, a more detailed analysis of HK-2 inhibition mediated cell death can provide deep understanding of the mechanism of action on oncosis/necroptosis axis. These findings provide an option to design clinically relevant and effective novel HK-II inhibitors and suggest the novel MJ analogues to study further as potential anti-cancer agents against GBM.